TOTAL ASET, RISIKO BISNIS, PERTUMBUHAN ASET DAN PROFITABILITAS TERHADAP HARGA SAHAM - Dendi Purnama; Dikdik Harjadi; Juwita Juwita (Medikonis, 2021)
ABSTRAK This study aims to analyze the effect of total assets, business risk, asset growth and profitability on stock prices. The research method used is descriptive and verification methods. The population in this study is the Mining sector, Crude Oil and Gas Sub-Sector and Coal Sub-Sector listed on the Indonesia Stock Exchange for the 2015-2018 period as many as 35 companies. Determination of the sample in this study using purposive sampling method. The number of samples in this study were 33 companies with a total of 132 company financial reports. The data analysis technique used panel data regression, coefficient of determination and hypothesis testing. The results of the study found that total assets, asset growth and profitability had a positive and significant effect on stock prices. Meanwhile, business risk has a negative and significant effect on stock prices.